팬데믹 이후 문해력 담론의 변화와 교육 정책적 함의 : 토픽 모델링과 시계열 분석을 중심으로 - 박고운; Park Goun; 최숙기; Choi Sookki (독서연구, 2025)
본 연구는 COVID-19 팬데믹 이후 한국 사회에서 문해력에 대한 언론 담론의 변화와 교육 정책적 함의를 분석하고자 한다. 2019년 1월부터 2024년 12월까지 수집된 4,304건의 뉴스 기사를 대상으로 LDA 토픽 모델링과 시계열 분석을 실시하였다. 분석 결과, ‘문해력 현황 진단’, ‘도서관 연계 독서 활동’, ‘AI 활용 문해력 정책’, ‘교과 문해력 지도’, ‘기초 문해력 국가책임 보장 체계’의 5개 주요 토픽이 도출되었다. 시계열 분석에서는 ‘도서관 연계 독서 활동’과 ‘AI 활용 문해력 정책’이 유의미한 상승세를 보인 반면, ‘기초 문해력 국가책임 보장 체계’는 감소 추세를 나타냈다. 연구 결과를 바탕으로 문해력 진단 평가 도구의 국가적 표준화, 교원의 문해력 지도 역량 강화, 지역사회 연계 독서 프로그램 확대, 교과별 차별화된 문해력 지도 전략 개발을 제언한다. This study analyzed changes in media discourse on literacy after the COVID-19 pandemic and their educational policy implications for Korean society. LDA topic modeling and time-series analysis were conducted on 4,304 news articles collected from January 2019 to December 2024. The analysis identified five major topics: “Literacy Status Assessment,” “Library-linked Reading Activities,” “AI-based Literacy Policy,” “Subject-specific Literacy Instruction,” and “National Responsibility System for Basic Literacy.” Time-series analysis revealed that “Library-linked Reading Activities” and the “AI-based Literacy Policy” showed significant upward trends, whereas the “National Responsibility System for Basic Literacy” displayed a downward trend. Based on these findings, the study proposes national standardization of literacy assessment tools, enhancement of teachers’ literacy instruction capabilities, expansion of community-based reading programs, and development of subject-specific literacy instruction strategies.